2016
DOI: 10.1016/j.xphs.2015.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sizes of Aggregates of Insulin Analogs and the Conformations of the Constituent Protein Molecules: A Concomitant Dynamic Light Scattering and Raman Spectroscopy Study

Abstract: To generate aggregates, 3 insulin analogs, lispro, aspart, and glulisine, were incubated without phenolic preservatives for 30 days at 37 °C. As a function of incubation time, aggregation was quantified with size exclusion chromatography, and the sizes of aggregates and the conformations of the constituent molecules were characterized with concomitant dynamic light scattering and Raman spectroscopy. During incubation, lispro was progressively converted into soluble aggregates with hydrodynamic diameters of cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…Apart from the formation of large fibrils, insulin solutions are also known to form much smaller aggregates in the nm region [26], an order of magnitude smaller than the formazin particles [36,37]. DLS was used to complement the UV turbidity analysis as it is a sensitive method for measuring such small-sized aggregates, 1 to 450 nm in diameter [38,39]. The time-dependent fluctuations in the scattering intensity as a result of Brownian motion are measured by DLS, the frequency of these fluctuations are used to determine particle diffusion coefficients and particle size [38].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the formation of large fibrils, insulin solutions are also known to form much smaller aggregates in the nm region [26], an order of magnitude smaller than the formazin particles [36,37]. DLS was used to complement the UV turbidity analysis as it is a sensitive method for measuring such small-sized aggregates, 1 to 450 nm in diameter [38,39]. The time-dependent fluctuations in the scattering intensity as a result of Brownian motion are measured by DLS, the frequency of these fluctuations are used to determine particle diffusion coefficients and particle size [38].…”
Section: Discussionmentioning
confidence: 99%
“…The second peak at ~100 nm can be assigned to small soluble rhBMP-2 nanoparticles. The height or area of both peaks cannot be used for particle quantification as light scattering intensity increases proportional to the power of six with the particle diameter and thus larger particles appear overrepresented [33]. For estimating the relative level of different size populations the volume distribution is more suitable.…”
Section: Size Of Soluble Rhbmp-2 and Rhbmp-2 Precipitates In Differenmentioning
confidence: 99%
“…Unfortunately, often the experimental conditions differ significantly from different authors, which creates certain difficulties in interpreting the results. In another study, Zhou et al showed that lispro aggregates faster than glulisine and aspart without stirring at the same temperature of 37°C, but different buffer conditions were used for each analogue [63]. Our data show that the insulin analogues form fibrils more slowly than insulin.…”
Section: Discussionmentioning
confidence: 49%